Alterations of relative telomere length and mitochondrial DNA copy number from ligamentum flavum-derived cells in lumbar spinal stenosis : Pilot study. - Dechsupa, S.; Singhatanadgige, W.; Limthongkul, W.; Yingsakmongkol, W.; Ittipanichpong , T.; Honsawek , S. (Chulalongkorn Medical Journal, 2023)
Background : Lumbar spinal stenosis is the common cause of low back pain in elderly people. It is characterized by hypertrophic ligamentum flavum (LF), a decrease of elastin-to-collagen ratio, and age-related fibrosis. Several studies have been reported that the telomere shortening, abnormality of mitochondrial DNA (mtDNA), and senescent cells were associated with age and degenerative diseases such as osteoporosis, osteoarthritis, and heart disease. However, the relative telomere length, mtDNA, and senescence mechanisms of human LF cells from lumbar spinal stenosis remain unclear. Objective : To determine the relative telomere length, mitochondrial DNA copy number (mtDNAcn), and cell senescence between non-pathologic and pathologic LF cells from lumbar spinal stenosis patients with various ages. Methods : We serially cultivated non-pathologic and pathologic human LF cells from 4 patients with various ages (61, 66, 77, and 84 years). During each subcultivation, we investigated relative telomere length and mtDNAcn by real-time polymerase chain reaction (PCR) and examined cell senescence markers by senescence-associated -galactosidase (SA- -gal) staining. Results : With advancing culture passages, there was a steady decline in the relative telomere length and mtDNAcn of non-pathologic and pathologic human LF cells. The elderly patients (84 years) had lower relative telomere length and mtDNAcn than the younger patients. Particularly, the elderly patients (77 and 84 years) had higher percentage of the SA- -galpositive human LF cells than the younger patients (61 and 66 years). Conclusions : There was a steady decline in the relative telomere length and mtDNAcn of human LF cells with advancing passages, irrespective of patient age. Senescent human LF cells accumulated in the LF with increasing age and pathologic tissue. These findings may provide a better understanding of pathogenesis of lumbar spinal stenosis.